1995
DOI: 10.1111/j.0022-3646.1995.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

PROTEIN PHOSPHATASE INHIBITORY ACTIVITY IN EXTRACTS OF CULTURED BLUE‐GREEN ALGAE (CYANOPHYTA)1

Abstract: A large‐scale screening program was initiated to evaluate laboratory‐cultured blue‐green algae (cyanobacteria) as a source of novel compounds with inhibitory activity against certain serine/threonine protein phosphatases. Over 1600 extracts, representing 816 cyanophyte strains with broad habitat and taxonomic diversity, were screened. Inhibitors were identified in extracts produced from all orders tested except Chamaesiphonales, and the family Stigonemataceae was found to contain proportionally more inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…To date, several potent inhibitors of PP1 and PP2A have been identified, including: okadaic acid, a polyether carboxylic acid produced by several species of marine dinoflagellates [11, 12]; >50 variants of microcystin, a family of cyclic heptapeptides produced by certain strains of cyanobacteria [13, 36, 37]; nodularin, a cyclic pentapeptide produced by Nodularia spumigena [24]; motuporin, a structural variant of nodularin [34]; calyculin A, a spiro ketal obtained from a marine sponge [39]; tautomycin, a dialkylmaleic anhydride produced by a strain of Streptomyces spiroverticillatus [40–42]; and cantharidin, an oxabicycloheptane‐2,3‐dicarboxylic acid anhydride that is a natural toxicant of blister beetles [17, 18]. This study confirms that fostriecin has inhibitory activity against PP2A and PP1, and shows that fostriecin has no apparent effect on the Ca 2+ /calmodulin‐dependent phosphatase, PP2B.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several potent inhibitors of PP1 and PP2A have been identified, including: okadaic acid, a polyether carboxylic acid produced by several species of marine dinoflagellates [11, 12]; >50 variants of microcystin, a family of cyclic heptapeptides produced by certain strains of cyanobacteria [13, 36, 37]; nodularin, a cyclic pentapeptide produced by Nodularia spumigena [24]; motuporin, a structural variant of nodularin [34]; calyculin A, a spiro ketal obtained from a marine sponge [39]; tautomycin, a dialkylmaleic anhydride produced by a strain of Streptomyces spiroverticillatus [40–42]; and cantharidin, an oxabicycloheptane‐2,3‐dicarboxylic acid anhydride that is a natural toxicant of blister beetles [17, 18]. This study confirms that fostriecin has inhibitory activity against PP2A and PP1, and shows that fostriecin has no apparent effect on the Ca 2+ /calmodulin‐dependent phosphatase, PP2B.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses have demonstrated that bloom toxicity is restricted to the phytoplankton N. spumigena (Laamanen et al , 2001; Moffitt & Neilan, 2001; Lyra et al , 2005), while the benthic Nodularia harveyana and Nodularia sphaerocarpa were demonstrated to be nontoxic (Lyra et al , 2005), with the exception of N. harveyana PCC7804 (Beattie et al , 2000; Saito et al , 2001). The toxicity of N. spumigena is due to the production of nodularin (Sivonen et al , 1989a, b), which is a potent hepatotoxin and putative tumor promoter (Honkanen et al , 1995; Sivonen & Jones, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these compounds are peptides (20,23) and have been reported to possess a number of bioactivities, such as toxicity for eukaryotic organisms and antimicrobial, antifungal, antiviral, and enzyme-inhibiting activities (2,11,22,23,31).…”
mentioning
confidence: 99%